(untitled) (Bangladesh Journal of Infectious Diseases, 2021)
Background: Microbiological confirmation of tuberculosis disease in children remains difficult due to paucibacillary disease and inability to obtain optimal samples. Recently introduced Cartridge based nucleic acid amplification test (CBNAAT) has improved microbiological diagnosis in pediatric tuberculosis. Objectives: We aimed to study association of CBNAAT grading based on cycle threshold value with conventional microbiological diagnosis. Methodology: This prospective study was conducted over a period from November 2016 to October 2017 in the Departments of Microbiology and Pediatrics, University College of Medical Sciences and Guru Teg Bahadur Hospital, Delhi. CBNAAT positive pediatric TB cases ≤12 years were recruited and subjected to Ziehl-Neelsen staining for acid fast bacilli (AFB) & culture on Lowenstein Jensen medium. CBNAAT positivity was graded based on cycle threshold value: very low, low, medium and high. Results: Smear and culture positivity was highest (100%) among specimens with high positive CBNAAT result based on CT value. Time to culture positivity was inversely related to CBNAAT grading (p=0.000). Conclusion: CBNAAT grading has significant positive association with smear and culture positivity. Bangladesh Journal of Infectious Diseases 2020;7(2):72-77